Th e Dynamics of Capabilities in the Transition to Telecommunications Next Generation Networks - Sato, Carlos Eduardo Yamasaki; Dergint, Dario Eduardo Amaral; Hatakeyama, Kazuo (Brazilian Journal of Operations & Production Management, 2010)
This paper examines the dynamics of capabilities in the transition to the socalled Next Generation Network (NGN), in the telecommunications industry. This transition is occurring in major incumbent fixed telecommunications operators like BT (British Telecom), France Telecom and Deutsche Telekom, among others, where the innovation gap seems to be more challenging compared to mobile operators and cable TV companies. We analyze the capabilities development of BT in the United Kingdom, using documentary and interview data. The main conclusion is that, during the transition, capabilities vary rapidly in intensity: at the very beginning, strategic capabilities infl uence the decision-making and defi ne the transition, and then project capabilities are put in place to deploy the strategy, until functional capabilities take over and maintain the evolutionary path of the technology until a next major transition may occur.